An Analysis of Student’s Speaking Problems in English Daily Communication Program at Islamic Boarding School - Rifqi Lativi, Nova; Hasnawan, Dedi (Perkumpulan Alumni dan Santri Mahyajatul Qurro’, 2023)
This research analyzed students’ speaking problems and the factors that caused the problems faced in English daily communication. This research used descriptive qualitative as the research design. The research subject was 30 students in the fourth grade of Al Iman Islamic Boarding School for Females. This research data was collected through observation, interviews, and questionnaires. To analyze the data, the researcher used three major phases of data analysis: data reduction, data display, and conclusion drawing/ verification. This study showed that each student faced different problems in speaking English daily. Some students faced inhibition, nothing to say, lack of participation, and mother tongue use. Where all the problems were caused by some factors called linguistic factors, psychological factors, and environmental factors that played important roles in supporting students in improving their speaking skills.